Vietnam following in China's footsteps: The third wave of emerging Asian economies - Jean-Raphael Chaponnière; Jean-Pierre Cling; Bin Zhou (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
Vietnam has been following China's path closely and very successfully for the last two decades, since the adoption of Doi moi in 1986. Over those last two decades, economic growth rates in both countries have been the highest worldwide (with GDP growing by 8 per cent and 10 per cent per year, respectively). The increase of the Vietnamese share of world trade is the highest of all major Asian exporters (including China) since the mid-1990s. In the current international context, doubts have been raised by some economists concerning the possibility for new Asian countries to take-off and join the group of emerging countries. Several obstacles might block this emergence, such as the rise of China and the stringent rules of the World Trade Organization (WTO). This paper addresses this question with regard to Vietnam, who joined the WTO at the beginning of 2007: we study Vietnam's potential for sustainable growth and international integration. We start by briefly describing economic reform and trade policies in Vietnam, and their results in terms of economic growth and world integration. We then analyse Vietnamese trade specialization and the bilateral relationship with China. Finally, we assess the competition between Vietnam and China on world markets, and show that the export structures are very different. Both countries have benefited from a boom in their textile and clothing exports following the cessation of quotas (in the case of China) and the signing of USBTA (in the case of Vietnam). For Vietnam, reducing the specialization in textiles and clothing, and joining the Asian production network in electronics, represents a major challenge.
Keywords: F13; O24; O53; 330; export-led growth; WTO; Vietnam; China; Wirtschaftswachstum; Wirtschaftsreform; Außenwirtschaftspolitik; Internationale Arbeitsteilung; Vietnam; China; China